Land suitability evaluation and soil management practices for oil palm yield improvement in Lake Victoria Region Uganda - Bonny Kayondo (2023)
Topography, rainfall, and soil physicochemical properties influence the performance of oil palm progenies and the subsequent soil management practices in a plantation. This has a significant impact on the productivity of oil palm plantations. Therefore, this study conducted in a mature oil palm plantation in Uganda from 2016 to 2021 enabled an understanding of the effect of the mentioned factors on the oil palm yield. The initial approach was a semi-detailed soil survey followed by land evaluation using the matching technique and the subsequent creation of maps for the various soils and their management groups. The study was done using a factorial randomized complete block design. The two factors in this study were two oil palm progenies and six soil management groups. Each of these factor combinations was replicated three times. The replicates represented the blocks of the experiment. This resulted in 36 experimental plots. Site-specific agronomic practices involving the use of organic and inorganic fertilizers, soil erosion control, and soil moisture conservation were done starting in the year 2017 until 2021. Rainfall data was obtained for ten years (2012-2021). Fresh fruit bunch yield data was recorded for the six years (2016-2021). This yield data was subjected to analysis of variance using SPSS software. Furthermore, the benefit-cost ratio was used to evaluate the financial performance of the Uganda and Malaysia plantations. The results showed that slope classes ranged from level (0-2°) to somewhat steep (20-25°), and the rolling (6-12°) covered 69.7% of the plantation. For soil, the sandy clay loam texture dominated (40%), cation exchange capacity ranged from low (2.10 cmol kg-1) to high (16.20 cmol kg-1), soil pH was mostly acidic (3.5-4.4) and organic carbon content ranged from low (1.17%) to high (4.05%). The mean annual rainfall (1,604 mm) was moderate with more than four dry months. There was a significant interaction (P<0.05) between the two progenies and the soil management groups for mean fresh fruit bunch yields, for the years 2016 and 2021. In the year 2021, the highest mean yields were obtained from the two largest soil management groups B (20.21 t ha-1), and A (19.46 t ha-1). The lowest yields were obtained from soil management groups Ait (18.03 t ha-1) and Bi (17.79 t ha-1). There was a significant difference (P<0.05) in fresh fruit bunch yield between the two progenies. Deli x Ghana produced a yield of 19.98 t ha-1 which was 13% or 2.38 t ha-1 higher than Guthrie D x P which produced 17.60 t ha-1. There was a significant difference (P<0.05) in yields between the years 2016 and 2021. The mean yield in 2021 was 21.46 t ha-1, which was 33%, or 5.34 t ha-1 higher than that of 2016, which yielded only 16.12 t ha-1. Benefit-cost ratio analysis results for the Uganda and Malaysia plantations were 3.20 and 2.19 respectively. Both investments are profitable but returns from the Uganda plantation were 32% more than that of the Malaysia plantation. Therefore, the site-specific agronomic practices that were implemented involving the use of both organic and inorganic fertilizers, soil erosion control, and soil moisture conservation increased the yields of the Uganda plantation. Besides cheap labour availability, the increase in yield of the Uganda plantation reduced the fresh fruit bunch and crude palm oil production costs per tonne. Therefore, implementation of standard site-specific agronomic practices to mitigate low soil fertility, soil erosion, and moisture deficit can lead to high and sustainable oil palm yields of the Uganda oil palm plantation. These practices should be maintained or improved for higher yields hence profitability of the plantation.